Controle de espécies de Poaceae e Convolvulaceae através de herbicidas aplicados em solo e palha e sensibilidade de mudas pré-brotadas de cana-de-açúcar - Santos, Paulo Henrique Vieira dos (Universidade Federal de São Carlos, 2021)
The implementation of the practice of raking straw in sugarcane fields resulted in heterogeneous distribution or total removal of straw in the areas. And these different amounts of straw can influence the floristic composition of weeds, resulting in a mixed flora, and the dynamics of herbicides applied under pre-emergence conditions. Then, the objective of this research was to test the hypothesis that pre-emergence herbicides applied in different amounts of sugarcane straw result in eficiente control and mass reduction of Urochloa decumbens (Stapf) R.D.Webster, Digitaria horizontalis Willd., Cenchrus echinatus L., Ipomoea triloba L. and Merremia aegyptia (L.) Urb and also to evaluate the sensitivity of sugarcane pre-sprouted seedlings (PSS) to herbicides applied in pre-planting. Weed control experiments were conducted in greenhouse, in a completely randomized design (CRD) in a 11+1 x 5 factorial scheme with four replications for each of the five weed species (Cenchrus echinatus, Urochloa decumbens, Digitaria horizontalis, Ipomea triloba e Merreia aegyptia) interacting with the herbicides isoxaflutole, clomazone, sulfentrazone, indaziflam, amicarbazone, tebuthiuron, s-metolachlor + [diuron + hexazinone], imazapic, amicarbazone + tebuthiuron, indaziflam + metribuzin e [indaziflam + isoxaflutole] and a control treatment and five different amounts of sugarcane straw (0, 2, 6, 8 e 10 t ha-1) with four replicates for each treatment. The experimental units were evaluated for the efficacy of control at 35 days after emergence (DAE) of the controls, when the plants were cut to obtain the dry mass of the aerial part (DMAP). The sensitivity experiment of sugarcane pre-sprouted seedlings was conducted in a greenhouse, in a completely randomized design (CRD) with the variety RB966928 receiving the application of the same herbicides used in the control experiment and four replicates for each treatment. The experimental units were evaluated for phytotoxicity weekly, number of leaves and height at the time of application and 63 days after application (DAA), when the seedlings were cut to obtain dry mass of the aerial part (DMAP). As for weed control experiments, it was observed that s-metolachlor + [diuron + hexazinone] and indaziflam + metribuzin satisfactorily control C. echinatus, U. decumbens and D. horizontalis, as well as sulfentrazone, tebuthiuron and amicarbazone + tebuthiuron satisfactorily control I. triloba and M. aegyptia, when applied in pre-emergence directly to the soil or sugarcane straw, reducing plant DMAP, on average, 95 and 98%, respectively. For the sensitivity experiment of pre-sprouted seedlings, different levels of tolerance of RB966928 to the herbicides used were observed, however, the use of clomazone, indaziflam, sulfentrazone and tebuthiuron, at 63 DAA, resulted in recovered plants and no changes in biometric parameters evaluated. The application of sulfentrazone in pre-planting of PSS, variety RB966928, is safe and efficient in the control of C. echinatus, U. decumbens, I. triloba and M. aegyptia.
Control of Poaceae and Convolvulaceae species through herbicides applied in soil and straw and sensitivity of sugarcane pre-sprout seedlings
Keywords: Corda-de-viola; Gramíneas; Manejo químico; MPB; Palhada; Saccharum spp.; RB966928; Morningglory; Grasses; Chemical control; PSS; Straw; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA